Engineering and Evaluation of Forcespun Gelatin Nanofibers as an Isorhamnetin Glycosides Delivery System - Elsy J. García-Valderrama; Narsimha Mamidi; Marilena Antunes-Ricardo; Janet A. Gutiérrez-Uribe; Karina Del Angel-Sanchez; Alex Elías-Zúñiga (MDPI AG, 2022)
Opuntia ficus-indica (L.) Mill (OFI) is considered a natural source of bioactive phytochemicals, mainly isorhamnetin glycosides (IRGs). These compounds have demonstrated antioxidant, anti-inflammatory, and anticancer activities, among others. The development of a suitable delivery system for these compounds is needed to improve their chemical and biological stability. This study aimed to evaluate the feasibility of fabrication and characterization of IRG-loaded gelatin (GL) forcespun fibers and crosslinking with glutaraldehyde (GTA). Two different percentages (25% and 30% w/v) of GL were evaluated with 12% (w/v) OFI flour to obtain nanofibers GL/OFI1 and GL/OFI2, respectively. The morphology and physicochemical properties of the fibers were investigated. The results indicated that the diameters of the fibers were on the nanoscale. The amount of IRGs was determined using high-performance liquid chromatography (HPLC). The IRGs release and the cytocompatibility of the nanofibers were also evaluated. GL concentration significantly affected the IRG release. Among both nanofibers, the GL/OFI2 nanofiber achieved a cumulative IRGs release of 63% after 72 h. Both fibers were shown to be biocompatible with human skin/fibroblast cells. Specifically, GL/OFI1 nanofibers exhibited favorable features for their application as an extract-coupled release system. The IRGs-embedded GL nanofiber mats may become a good alternative for the delivery of phytochemicals for the health sector and biomedical applications.